The Study of Quality of Life in Patient with Vitiligo - Poudyal, Yogesh; Parajuli, Niraj; Dahal, Sudip Chandra; Jha, Chandra Bhal (Birat Journal of Health Sciences, 2020)
Introduction: Vitiligo is an acquired, idiopathic and common de-pigmentation disorder of skin. Strong stigma associated with the disease, its chronic nature, and cosmetic disfigurement often cause distress to patients and may affect the quality of life. Objective: To assess the quality of life in patient with vitiligo, using Dermatology life quality index(DLQI) questionnaire. Methodology:Total of 212 patients with vitiligo participated in this cross- sectional study done at Dermatology and Venereology OPD of Universal College of Medical Science, Bhairahawa, Nepal.. The participants were given DLQI questionnaire consisting of 10 questions to fill up. Result:The median DLQI score was 4(6), which showed small effect in quality of life. There was positive association with duration of disease and DLQI score (p˂ 0.05). The highest average score was seen in heading item “symptom and feeling”.There was no difference in DLQI score, when compared among gender and among various types of vitiligo. Conclusion: Psychological assessment should be done in vitiligo cases, especially in those with long duration of disease.